Prevalence of electrocardiographic changes in patients with acute aneurysmal subarachnoid hemorrhage and their relationship with outcome - Saktheeswaran Mahesh Kumar; Dinesh Choudhary; Ajeet Arulkumar; Thajudeen Anees; Suresh Nair; Jaganmohan A. Tharakan (Indian Journal of Neurosurgery)
Background Electrocardiographic (ECG) alterations occurring after subarachnoid hemorrhage (SAH) have been described frequently, but the prognostic significance of these changes has not been well characterized.